Comparing Mental Health During the COVID-19 Lockdown and 6 Months After the Lockdown in Austria: A Longitudinal Study - Pieh, Christoph; Budimir, Sanja; Humer, Elke; Probst, Thomas (Frontiers in Psychiatry, 2021)
The novel Coronavirus disease (COVID-19) has repeatedly been reported to impair mental health. This longitudinal study evaluated mental health at the emergence of the COVID-19 pandemic (t1) and six months later (t2) in Austria. Indicators of mental health were depression (PHQ-9), anxiety (GAD-7), sleep quality (ISI), perceived stress (PSS-10), as well as the quality of life (WHO-QOL BREF), and well-being (WHO-5). In total N=437 individuals participated in both surveys (52.9 % women). The number of participants with clinically relevant depressive-, anxiety-, or insomnia symptoms did not differ statistically significantly between t1 and t2 (p≥ .48). The prevalence of moderate or severe (clinically relevant) 1) depressive symptoms changed from 18.3% to 19.7% (p= .48), 2) clinically relevant anxiety symptoms from 16.5% to 15.6% (p= .67), and clinically insomnia from 14.6% to 15.6% (p= .69) from t1 to t2. Bonferroni-corrected t-tests showed that the stress level (PSS-10) decreased, and well-being (WHO-5) increased. However, effect sizes seem clinically not relevant (Cohen`s d <0.2). Results suggest that detrimental health consequences of the COVID-19 pandemic persisted several months after its outbreak and the end of the lockdown measures, respectively. Regarding well-being and stress, there is a slight trend in improvement.